Biophilia and Biophobia as Emotional Attribution to Nature in Children of 5 Years Old - Olivos-Jara, Pablo; Segura-Fernández, Raquel; Rubio-Pérez, Cristina; Felipe-García, Beatriz (Frontiers in Psychology, 2020)
Introduction: Connectedness to nature is a concept that reflects the emotional relationship between the self and the natural environment, based on the theory of biophilia, the innate predisposition to the natural environment. However, the biophobic component has largely been ignored, despite, given its adaptive functional role, being an essential part of the construct. If there is a phylogenetic component underlying nature connectedness, biophilic and/or biophobic, there should be evidence of this record from early childhood. The main aim of this study is therefore to describe the emotional attributions identified in five-year-olds. Methodology: Two studies were conducted. In the first, 94 children expressed their concept of nature and made basic emotional attributions to a set of 60 images of natural and urban environments, using a software designed for the study. In the second, 39 children repeated the procedure and provided explanations for their responses. Results: The main results show that, in general, children use both positive and negative emotions, which may be related to a three-dimensional model of emotional attributions to nature. The most widely attributed emotion is happiness, for the images of both natural and built environments. However, fear is the second most common attribution. The role of happiness could be explained by a feeling of security and familiarity that the habitat of the built environment contributes to, while the importance of fear in nature could show an adaptive response of the fear of wild nature in children. This interpretation could be confirmed when analyzing specifically the emotional attributions to the natural environment, classifying the images according to biological and ecosystemic criteria. Thus, for example, more emotional attributions are explained by the "pleasantness" attributed to primary producers and landscapes (e.g. flora), versus attributions of "harm" to the images of secondary and tertiary consumers (e.g. hunters). Conclusions: These results provide evidence in favor of a didactic procedure to study emotional attributions to images of nature in preschool children. They suggest the incorporation of biophobia as an important adaptive factor in connectedness to nature and a tripartite emotional hypothesis based on the valences of the attributed emotions.